Monopolistic supply of sorting, inequality, and welfare - Lisa Windsteiger (Journal of Public Economic Theory, 2021)
Why is an increase in income inequality often accompanied by an increase in socioeconomic segregation? And what are the welfare implications of this comovement? This paper uses a theoretical model to analyze the relationship between income inequality and socioeconomic segregation. It shows that rising inequality can trigger sorting according to income, as a monopolist's profits from offering sorting increase with income inequality. It also examines the relationship between sorting and social welfare and shows that profit-maximizing sorting patterns are not necessarily optimal from a welfare perspective. In fact, for a broad field of income distributions (monopolist) profits increase with inequality, while at the same time total welfare from sorting decreases.
Keywords: 330